BHCMDA: A New Biased Heat Conduction Based Method for Potential MiRNA-Disease Association Prediction - Zhu, Xianyou; Wang, Xuzai; Zhao, Haochen; Pei, Tingrui; Kuang, Linai; Wang, Lei (Frontiers in Genetics, 2020)
Recent studies have indicated that microRNAs (miRNAs) are closely related to sundry human sophisticated diseases. According to the surmise that functionally similar miRNAs are more likely associated with phenotypically similar diseases, researchers have proposed a variety of valid computational models through integrating known miRNA-disease associations, disease semantic similarity, miRNA functional similarity, and Gaussian interaction profile kernel similarity to discover the potential miRNA-disease relationships in biomedical researches. Taking account of the limitations of previous computational models, a new computational model based on Biased Heat Conduction for MiRNA-Disease Association prediction (BHCMDA) was proposed in this paper, which can achieve the AUC of 0.8890 in LOOCV (Leave-One-Out Cross Validation) and the mean AUC of 0.8931±0.0007 under the framework of 5-fold Cross Validation respectively. In addition, BHCMDA was further implemented to the case studies of three vital human cancers, and simulation results illustrated that there are 88% (Esophageal Neoplasms), 92% (Colonic Neoplasms) and 92% (Lymphoma) out of top 50 predicted miRNAs having been confirmed by experimental literatures separately, which demonstrated the good performance of BHCMDA as well. Thence, BHCMDA would be a useful calculative resource for potential miRNA-disease association prediction.